The feeling of the story: Narrating to regulate anger and sadness. Issue 3 (3rd April 2017) - Pasupathi, Monisha; Wainryb, Cecilia; Mansfield, Cade D.; Bourne, Stacia
ABSTRACT: Admonitions to tell one's story in order to feel better reflect the belief that narrative is an effective emotion regulation tool. The present studies evaluate the effectiveness of narrative for regulating sadness and anger, and provide quantitative comparisons of narrative with distraction, reappraisal, and reexposure. The results for sadness ( n  = 93) and anger ( n  = 89) reveal that narrative is effective at down-regulating negative emotions, particularly when narratives place events in the past tense and include positive emotions. The results suggest that if people tell the "right" kind of story about their experiences, narrative reduces emotional distress linked to those experiences.